ANALYSIS EFFECT OF FUNDING DECISION, INVESTMENT DECISION AND DIVIDEND POLICY ON VALUE COMPANY - Rakhmawati Oktavianna; Utari Mega Pratiwi (JASS (Journal of Accounting for Sustainable Society), 2022)
ABSTRACT This study aims to obtain empirical evidence of the effect of funding decisions, investment decisions, and dividend policies on company value in financial companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This type of research is quantitative. The population in this study are financial companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This sampling technique uses purposive sampling, that is, the data collection is adjusted to a predermined withdrawal. The samples obtained from this study were 24 companies. The statistical test used is the Data Regression Analysis Panel. Data analysis techniques in this study were processed using the Eviews statistical software program version 10. Based on the results of the hypothesis testing that has been done, it was found that Funding Decisions, Investment Decisions, and Dividend Policy have a simultaneous effect on Firm Value Partially, Funding Decisions and Investment Decisions have an effect on Firm Value, while Dividend Policy has no effect on Firm Value